Dynamic biomechanical analysis of vocal folds using pipette aspiration technique - Scheible, Florian; Lamprecht, Raphael; Semmler, Marion; Sutor, Alexander (Sensors, 2021)
The voice producing process is a complex interplay between glottal pressure, vocal folds, their elasticity and tension. The material properties of vocal folds are still insufficiently studied, because the determination of material properties in soft tissues is often difficult and connected to extensive experimental setups. To shed light on this less researched area, in this work, a dynamic pipette aspiration technique is utilized to measure the elasticity in a frequency range of 100–1000 Hz. The complex elasticity could be assessed with the phase shift between exciting pressure and tissue movement. The dynamic pipette aspiration setup has been miniaturized with regard to a future in-vivo application. The techniques were applied on 3 different porcine larynges 4 h and 1 d postmortem, in order to investigate the deterioration of the tissue over time and analyze correlation in elasticity values between vocal fold pairs. It was found that vocal fold pairs do have different absolute elasticity values but similar trends. This leads to the assumption that those trends are more important for phonation than having same absolute values.
CRIS-Team Scopus Importer:2021-04-30
Keywords: Elastic modulus; Frequency-dependent material properties; Larynx; Laser vibrometry; Phonation; Pipette aspiration; Vocal folds; Young’s modulus